Thermal Analysis of a Ground Passive Cooling (GPC) Using Experimental Method - T. M., Yusof; S., Anuar; Hassan, Ibrahim (2015)

(untitled)
Ground temperature gets attenuated as the depth of the ground increase and become constant throughout the year at a sufficient depth. On the low side of the ground temperature relative to the ambient, it can be utilized for space cooling by means of ground passive cooling (GPC) technique. GPC technique is a method requires a pipe or several pipes buried below the ground surface at which temperatures are lower than outside ambient temperature. By circulation ambient air inside the pipe, heat will be rejected from the air inside the pipe to the ground surrounding. Performance of the GPC is crucial and it is depend on the local ground temperature, ground thermal properties and the GPC’s pipe specification. Since the ambient temperature in Malaysia during the daytime is ranging from 30 to 35°C, thus it has a great potential for implementing GPC as an alternative method in building cooling. Ground temperature in Malaysia has been analyzed and it is depend on depth, thermal diffusivity and time and it is lower than the ambient temperature at certain depth. Therefore, it has capability to serve cooling by mean of GPC. This paper presents the performance of GPC in term of outlet temperature and rate of heat transfer based on mathematical model and experimental study. Different input parameters have been investigated such as depth of the ground, input temperature and flowrate of the air inside the pipe. Experimental rig of the GPC has been developed with the main purpose to create actual ground condition. A PCV pipe with 8.7 m length has been used in the experiment. Results show that flowrate at 0.03 kg/s and Tg = 23°C gives great temperature reduction in the pipe compared with higher flowrate and ground temperature. Highest rate of heat transfer of 473 W occurred at flowrate of 0.07 kg/s and Tg = 23°C. The experimental results also have been validated with mathematical model and obtained close agreement.